Salification-driven strategy toward the hydrophobic molecular salt of the antifungal drug 5-fluorocytosine and protocatechuic acid with triple-helix structure offers an innovative insight for conquering adverse drug reactions. Issue 13 (13th March 2023) - Bu, Fan-Zhi; Yu, Yue-Ming; Zhang, Lin-Lin; Yan, Cui-Wei; Wu, Zhi-Yong; Li, Yan-Tuan
Abstract : The hydrophobic molecular salt of 5-fluorocytosine (FYT) with protocatechuic acid (PCA) was first reported, and its dissolution behaviors were systematically studied by combining theory with experiment. Abstract : The goal of the present work is to elucidate the ability of protocatechuic acid (PCA) in downregulating the dissolubility property and gain an innovative insights into conquering adverse reactions of the antifungal drug 5-fluorocytosine (FYT) by a salification strategy. The strategy highlights the feature of adjacent 3, 4-substituted phenolic groups on PCA molecule that establishes the helical morphology to attain the hydrophobic molecular salt by facilitating proton exchange reaction between PCA and FTY, thus decreasing FYT's dissolution capacity; moreover, it can also play to PCA's strengths with hepatoprotective effect and antifungal potential as a phenolic acid nutrient, all of which benefit in overcoming the adverse drug reactions caused by the fast and inappropriate absorption of FYT. Taking the strategy as a guideline, the first FTY's molecular salt, FTY–PCA, with hydrophobic characteristics has been successfully synthesized and thoroughly characterized by multiple analytical approaches. The single-crystal X-ray diffraction technology verifies that the newly obtained FTY–PCA consists of an unusual hydrophobic triple helix structure (THS) that is dexterously wound by three strands single helix structure (SHS) via robust hydrogen-bonding interplays and electrostatic forces, which endows the ability of concurrent downregulation of the solubility and dissolution rate, with the maximum reduction being, respectively, 31.23% and 60.49% relative to the parent drug FYT. The experimental outcomes are strongly confirmed by relevant theoretical studies. The molecular electrostatic potential confirms that the THS motif constructed by the SHS forms serves a crucial role in reducing the polarity of the molecular salt and complies with the abatement in polarity, attributable to the reinforced hydrogen-bonding energy as per the electron density difference as well as topology analysis of atoms in molecules, thereby clarifying the hydrophobic property of the molecular salt at theoretical levels. Thereby, the current contribution not only exemplifies the first hydrophobic molecular salt of FYT with a rare triple-helical structure, filling the gaps in the application of hydrophobic molecular salt in antifungal drugs, but also supplies some novel insights into the salinization strategy aiming at overcoming the adverse effects caused by the fast and almost entire absorption of some drugs by ameliorating the dissolubility behaviors.